2019
DOI: 10.1097/fbp.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of synthetic cathinone 3,4-methylenedioxypyrovalerone persistently increases impulsive choice in rats

Abstract: 3,4-Methylenedioxypyrovalerone (MDPV) is a selective catecholamine reuptake inhibitor abused for its psychostimulant properties. This study examined if MDPV administration alters impulsive choice measured by delay discounting in rats. Three groups of rats were tested in daily delay discounting sessions to determine the effects of acute cocaine (1.0–30.0 mg/kg), MDPV (0.1–3.0 mg/kg), or saline on mean adjusted delay (MAD). Dose-dependent decreases in MAD were elicited only by acute MDPV, which also suppressed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 74 publications
2
6
0
Order By: Relevance
“…38,39 Hyatt et al ( 2019), one of the first papers to describe the effects of MDPV on impulsivity, found that acute administration of MDPV, but not cocaine, led to increases in choice impulsivity in a delay-discounting task. 40 Hyatt et al (2020) then reported that both MDPV and cocaine consistently increased impulsive action in a differential reinforcement of low rates of responding task, similar to the effects observed in the 1-CSRTT. 41 While the current study mostly aligns with the results of these papers, the increase in impulsive action after acute administration of increasing doses of each drug was not as robust, which is different from that found in previous studies.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…38,39 Hyatt et al ( 2019), one of the first papers to describe the effects of MDPV on impulsivity, found that acute administration of MDPV, but not cocaine, led to increases in choice impulsivity in a delay-discounting task. 40 Hyatt et al (2020) then reported that both MDPV and cocaine consistently increased impulsive action in a differential reinforcement of low rates of responding task, similar to the effects observed in the 1-CSRTT. 41 While the current study mostly aligns with the results of these papers, the increase in impulsive action after acute administration of increasing doses of each drug was not as robust, which is different from that found in previous studies.…”
Section: Discussionmentioning
confidence: 83%
“…41 While the current study mostly aligns with the results of these papers, the increase in impulsive action after acute administration of increasing doses of each drug was not as robust, which is different from that found in previous studies. 38,40,41 In addition, the amount of premature responses and food reinforcers earned decreased (and thus omissions increased) at the largest doses of cocaine and MDPV tested. Similar results were reported in Hyatt et al (2020), but operant responding suppression in the current study occurred at lower doses than what was observed in the Hyatt study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, recent studies have shown the benefits of antiinflammatory agents for neuropsychiatric disorders [111,112]. Exposure to drugs of abuse is also known to disrupt brain dopamine systems and dopamine-related behavior [113][114][115], which may be reversible with DHA treatment. DHA and other O3FA are ligands for nuclear receptors such as the retinoid X receptor (RXR) [116].…”
Section: Neuroprotective Effects Of O3famentioning
confidence: 99%
“…The relative activation of these two systems is associated with choices in delay discounting procedures (McClure, Laibson, Loewenstein, & Cohen, 2004). Other research suggests that a range of additional biological and genetic factors can play a role in discounting rates (Anderson & Woolverton, 2005; MacKillop, 2013; Mitchell, 2004; Rung & Madden, 2018) including systemic administration of drugs of abuse (Dallery & Locey, 2005; Helms, Reeves, & Mitchell, 2006; Hyatt et al, 2019; Xue, Siemian, Johnson, Zhang, & Li, 2018). Early life adversity has also been linked to steep discounting and SUDs (Acheson, Vincent, Cohoon, & Lovallo, 2019).…”
mentioning
confidence: 99%